Peer Social Support and Self-Esteem as Subjective Well-Being Predictors of Late Adolescents in Bandar Lampung - Ulfa Jauhari, Rosy Maria; Izzaty, Rita Eka; Jauhari, Tontowi; Sabza Gol Qaderi (Universitas Muhammadiyah Yogyakarta, 2026)
Late adolescents experience academic and social pressures that may influence their subjective well-being. However, evidence on the roles of peer social support and self-esteem in Muhammadiyah senior high schools remains limited. Therefore, this study examined the influence of peer social support and self-esteem on the subjective well-being of late adolescents. This study employed a quantitative, ex post facto approach. The research was conducted in Bandar Lampung, Indonesia, with a sample of 150 late adolescents. Sample selection in this research used a random sampling technique. In contrast, data collection used a subjective well-being scale (reliability = 0.898), a peer social support scale (reliability = 0.878), and a self-esteem scale (reliability = 0.842). Data analysis was performed using multiple regression analysis. The results showed a significant effect of peer social support on self-esteem and late adolescent subjective well-being, accounting for 44.3%. Variables related to peer social support and self-esteem played an important role in shaping subjective well-being among late adolescents. This study offers a novelty by simultaneously examining both variables within a population of late adolescents in a Muhammadiyah-based educational setting. The findings highlight the importance of developing school-based interventions that strengthen supportive peer relationships and foster positive self-esteem to enhance students' subjective well-being, particularly in faith-based educational contexts